Evaluation of virulence factors of strains of Salmonella Typhimurium isolated from diseased and healthy guinea pigs (Cavia porcellus) - Duran Gonzalez, Carla (2021)
The present study evaluated the presence of 10 genes encoding various virulence factors of biological importance in 100 Salmonella Typhimurium isolates, where 90 isolates came from sick guinea pigs and 10 from apparently healthy ones. DNA was extracted from all isolates and analyzed using the Multiple PCR technique to assess the presence of the spvB, spiA, cdtB, sipB, tolC, sitC, lpfC, sifA, sopB and pefA genes. A similar genetic pattern was obtained, with variable detection frequencies greater than 60%, both in healthy and sick guinea pigs, except for the cdtB gene, which was not detected. There were no significant differences between the presence of Salmonella Typhimurium virulence factors isolated from sick guinea pigs and apparently healthy guinea pigs.